Failure Criteria in Crashworthiness Analysis of Ship Collision and Grounding Using FEA: Milestone and Development - Hermes Carvalho; Ridwan Ridwan; Sudarno Sudarno; Aditya Rio Prabowo; Dong Myung Bae; Nurul Huda (Universitas Sebelas Maret, 2023)
This study presents reviews of the failure criteria to capture the resulting response due to the catastrophe of ship collision and grounding using the finite element. Researchers have introduced several failure criteria, for instance, the Det Norske Veritas (DNV) RP-C204 criterion, Germanischer Lloyd criterion, Peschmann, Rice-Tracey and Cockcroft-Latham (RTCL), Bressan-Williams-Hill (BWH) instability criterion, and Liu criterion. As in the mathematical formula, each criterion has a difference. The choice of failure criteria will depend on the simulation's specific requirements and the analysis's goals. Liu's criterion can be used to evaluate the failure of materials in ship collision simulations, for example, when large element sizes (i.e., 20 mm) are considered in the simulation.